The Organisation for the Harmonisation of Business Law in Africa (OHADA) System: Overview of some Benefits and Problem Areas - Leno, Ngaundje Doris (International Journal of Advanced Research and Publications, 2018)
As much as the Organisation for the Harmonisation of Business Law in Africa (OHADA) aims to improve the legal environment for business, the harmonisation process should be seen as a tool of economic integration with several advantages. Despite the achievements and benefits, OHADA, like other regional integration efforts in Africa, has some temporary drawbacks that may become permanent if no effort is made to overcome them. The primary focus of the paper is to present OHADA‟s background; offer an overview of some of the salient benefits of OHADA‟s institutional and regulatory framework; consider OHADA‟s problem areas; and propose possible solutions to the problems. The value of the paper, therefore, lies in the insight it offers into OHADA, the benefits and problems of its institutional and regulatory framework. It is also important because it is laying the foundation in making the OHADA structure available for all Africans.
Keywords: Business law; Harmonisation; OHADA

Regionalism : lessons the SADC may learn from OHADA - Leno, Ngaundje Doris (THRHR, 2012)
Meeste Afrikastate is klein en het nie die vermoë om effektief aan prosesse van die Wêreldhandelsorganisasie deel te neem nie. Hierdie onvermoë, saam met ander faktore, is die hoofrede vir die voortgesette marginalisering van die kontinent in die globale ekonomie en handel. Ten einde effektief aan genoemde prosesse deel te neem en in die voordele van die geglobaliseerde wêreld te deel, moet Afrikastate integreer. Regionalisme of integrasie is nie ’n doel op sigself nie maar is nodig vir die ekonomiese groei van Afrikastate. Dit skep groter markte vir handel en belegging en is ’n aansporing tot groter effektiwiteit, produktiwiteit en mededingendheid. In die lig hiervan stel die artikel drie kernargumente. Die eerste is dat regionalisme voordele bied wat Afrikastate kan ontgin ten einde marginalisering op globale vlak te oorkom. Die tweede argument is dat, terwyl die Suider-Afrikaanse Ontwikkelingsgemeenskap (SAOG) poog om besigheidsreg te harmoniseer, die Organisation for the Harmonisation of Business Law in Africa (OHADA) (Organisation pour l’Harmonisation en Afrique du Droit des Affaires) as voorbeeld kan dien aangesien dit reeds die grondslag gelê het vir die harmonisering van besigheidsreg in Afrika. Die derde argument is dat die SAOG-tribunaal verbeter moet word ten einde ’n meer regionale regsraamwerk binne die SAOG daar te stel. In hierdie verband belig die artikel sommige voordele van regionalisme in Afrika, die lesse wat die SAOG by OHADA kan leer, die voordele van ’n geharmoniseerde besigheidsreg teen die agtergrond van die OHADA-ondervinding en die moontlike wyses waarop die SAOGtribunaal verbeter kan word.

Development of a uniform insolvency law in SADC : lessons from OHADA - Leno, Ngaundje Doris (Journal of African Law, 2013)
This article argues that, with the global or cross-border nature of many corporate activities, there is an increasing need for a uniform insolvency law approach to the financial distress of a corporation in the Southern African Development Community. In doing so, the article highlights lessons the community may learn from the Insolvency Act of the Organisation for the Harmonization of Business Law in Africa. Emphasis is given to that organization’s success in developing a uniform insolvency act (ie one which is directly applicable in its contracting states). The article also proposes a number of recommendations.
Accepted: 2014-02-28T11:57:54Z
Keywords: Africa; Bankruptcy; Business law; Financial distress; Insolvency Act; Insolvency law

The development of a commercial law structure in the SADC with specific reference to OHADA - Leno, Ngaundje Doris (University of Pretoria, 2013)
In a region where there is diversity of laws, the author maintains that law reform is a catalyst for investment and development. This thesis aims at demonstrating that OHADA provides practical lessons for the development of a uniform commercial law structure in the SADC. This is following OHADA’s success in developing uniform commercial rules that are directly applicable in the contracting states. To achieve this, the thesis uses a “structured focused comparison” methodology that allows for two separate, but structurally linked accounts of the structures of both organisations. In exploring the structures of both organisations, the thesis endeavours to: determine whether there is the need for the development of a commercial law structure in the SADC; whether such a structure can be developed within the current SADC structure and whether OHADA can serve as a possible model for the SADC. The findings show that no part of the African continent has witnessed regional legal reform on the scale of that initiated by OHADA. It equally reveals the absence of a uniform commercial law structure in the SADC and the lack of supranational structures to adopt full panoply of business laws and to preserve the uniformity of laws in the member states. The findings from this thesis provide evidence that there is the need forthe development of a commercial law structure in the SADC and improvement of the current SADC structure. There is no doubt that thi swould do away with legal uncertainty in cross-border commercial transactions among SADC states.
Accepted: 2016-05-20T09:04:41Z URI: https://repository.up.ac.za/handle/2263/52731